School Students’ Self-confidence in Science and Intrinsic Motivation for Learning Science: Self-Concept and Self-Efficacy Approach - Pečiuliauskienė, Palmira (Pedagogika, 2020)
The study deals with the Lithuanian school students’ self-confidence in science and motivation for learning science on the basis of TIMSS 2015 data. The study analyses two components of self-confidence: science self-concept (SSC) and science self-efficacy (SSE). The research revealed that self-confidence in science of school students statistically significant correlate with the motivation for learning science.